2019
DOI: 10.1007/s12571-019-00970-7
|View full text |Cite
|
Sign up to set email alerts
|

Developing fruit tree portfolios that link agriculture more effectively with nutrition and health: a new approach for providing year-round micronutrients to smallholder farmers

Abstract: A sufficient intake of fruits can alleviate micronutrient deficiencies and reduces the risks of a number of associated diseases. In many parts of sub-Saharan Africa, however, the production and consumption of fruits are inadequate on average and in particular so in specific seasons. To better incorporate fruits into local food systems while addressing the challenge of seasonal availability, World Agroforestry (ICRAF) has developed a methodology based on “fruit tree portfolios” that selects socio-ecologically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…East African farms often feature wild, indigenous (semi-domesticated) and domesticated fruit trees, either on the farm or in its vicinity. In Eastern Kenya, over half of the fruit trees found on farms were found to be indigenous fruit trees [ 35 ]. A wide range of other wild and indigenous fruit trees is also found off-farm [ 23 ]; however, this is not reflected in the consumption patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…East African farms often feature wild, indigenous (semi-domesticated) and domesticated fruit trees, either on the farm or in its vicinity. In Eastern Kenya, over half of the fruit trees found on farms were found to be indigenous fruit trees [ 35 ]. A wide range of other wild and indigenous fruit trees is also found off-farm [ 23 ]; however, this is not reflected in the consumption patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in the same region found a positive correlation between fruit tree diversity and decreasing farm size, mainly attributed to the multi-purpose possibilities offered by many trees [ 41 ]. Trees can provide not only foods such as fruits, but also timber, medicines, fodder and different ecosystem services [ 35 ]. Nyaga et al [ 42 ], found that the diversity of fruit tree species increased with decreasing resource endowment.…”
Section: Discussionmentioning
confidence: 99%
“…The quantity, frequency and type of forest food used varies greatly from one place to the next (Powell et al 2015;Rowland et al 2016): from occasional supplementation to a very high level of dependence. The diversity of plant species in tree-based systems and the differences in their fruiting phenology help ensure all year-round food availability, including availability of particular micronutrients, such as vitamins (Vira et al 2015;McMullin et al 2019). Forests and trees, used as a reserve of fodder, can support livestock production and increase animal-sourced food consumption among poor rural communities living in or near forests.…”
Section: Availabilitymentioning
confidence: 99%
“…For instance, a wider diversity of fruit tree species in agroforestry systems can help prevent or limit seasonal shortages in fruit supply (Jamnadass et al 2011;Vinceti et al 2013;McMullin et al 2019).…”
Section: Stabilitymentioning
confidence: 99%
“…And further, soils with increased nutrients can translate into micronutrients in food (Frossard et al 2000 , Lal 2009 , Arhin and Kazapoe 2017 , Wood et al 2018 ). The inclusion of fruit trees in agroforestry systems is also important to improving fruit consumption (McMullin et al 2019 ).…”
Section: Empirical Basis For the Role Of Forests And Trees In Dietarymentioning
confidence: 99%